Pathophysiological role of calcium channels and transporters in the multiple myeloma - Tingting Li; Junmin Chen; Zhiyong Zeng (Cell Communication and Signaling, 2021)
Abstract Multiple myeloma (MM) is a common malignant tumor of plasma cells. Despite several treatment approaches in the past two decades, MM remains an aggressive and incurable disease in dire need of new treatment strategies. Approximately 70–80% of patients with MM have myeloma bone disease (MBD), often accompanied by pathological fractures and hypercalcemia, which seriously affect the prognosis of the patients. Calcium channels and transporters can mediate Ca2+ balance inside and outside of the membrane, indicating that they may be closely related to the prognosis of MM. Therefore, this review focuses on the roles of some critical calcium channels and transporters in MM prognosis, which located in the plasma membrane, endoplasmic reticulum and mitochondria. The goal of this review is to facilitate the identification of new targets for the treatment and prognosis of MM. Video Abstract